The influence of delay elimination communication on the prevalence of primary nocturnal enuresis—a survey from Mainland China. Issue 5 (18th April 2019) - Wang, Xi Zheng; Wen, Yi Bo; Shang, Xiao Ping; Wang, Yi He; Li, Yan Wei; Li, Tian Fang; Li, Shou Lin; Yang, Jing; Liu, Yan Jin; Lou, Xiao Ping; Zhou, Wei; Li, Xing; et al.
Abstract: Aims: A pilot survey shows that primary nocturnal enuresis (PNE) prevalence has increased significantly during the past decade in Mainland China. Whether it is related to the delay of elimination communication (EC) is unclear. This study retrospectively investigated the influence of delayed EC on the PNE prevalence in children and adolescents in mainland China. Methods: A cross‐sectional study of PNE prevalence was performed by distributing 19 500 anonymous self‐administered questionnaires to parents in five provinces of mainland China from July 2017 to October 2017. The questionnaires included sociodemographic data, family caregivers' information, and details about the disposable diapers (DD) usage, EC commencement date, psychological disorders, lower urinary tract symptoms, and family history of PNE in children and adolescents. The 2017 PNE prevalence was compared with that of 2006 in Mainland China. Results: The total response rate was 97.04% (18 631 of 19 500) and 92.39% (18 016 of 19 500) qualified for statistical analysis. The PNE prevalence in 2017 has increased significantly compared to that of 2006 (7.30% vs 4.07%, P  < 0.001). The PNE prevalence in children with EC starting before 6 months of age was significantly lower than those who start after 12 months of age. The longer DD were used and the later the beginning of EC, the higher the PNE prevalence was found. Conclusions: The PNE prevalence in Mainland China has increased significantly during the past 10 years. A longer use of DD and later onset of EC may be risk factors for PNE.